PENGAJARAN MEMBACA DAN MENULIS BAGI PESERTA DIDIK TUNARUNGU - Rofiah, Khofidotur (Jurnal Pena Indonesia, 2016)
Reading and writing skills is coverage of more complex language skills of listening and speaking skills. We need the best approach in developing the literacy skills of children with hearing impairment. In some studies that focus on accuracy syntax hearing impaired children, it was found that they tend to use many of the same phrases over and over again in simple sentences, a little more complex sentences, and make lots of small mistakes in the use of sentence structure, word number, the use of pronouns and said pointer, and so on. This paper discusses several options approach in teaching reading and writing skills of deaf children, namely (1) conversations from heart to heart (perdati), (2) read ideovisual (percami), (3) read receptive, (4) the exercise of reflective, and (5) conversation or conversations linguistic grammar or also called reflective conversation grammar.